Evidence of porcine circovirus‐like virus P1 in piglets with an unusual congenital tremor. Issue 2 (27th November 2017) - Wen, L.; Mao, A.; Jiao, F.; Zhang, D.; Xie, J.; He, K.
Summary: Outbreaks of trembling and shaking were reported among pigs at two pig farms in Jiangsu Province, China. Serum and tissue samples tested positive for porcine circovirus‐like virus P1 and negative for classical swine fever virus, porcine circovirus type 2, astrovirus and porcine pestivirus using PCR/RT‐PCR and immunohistochemical techniques. High P1 viral genome loads were identified in sera, brain and lymph node tissue samples by qPCR. In addition, one of the most notable pathological changes was dissolution of the nucleus in Purkinje cells. The results of this study provide molecular evidence of an association between congenital tremor in pigs and P1 virus.